Oral Signs of Tropical, Fungal, and Parasitic Diseases - Pérez-Alfonzo, Ricardo; Alencar-Marques, Silvio [UNESP]; Giansante, Elda; Guzmán-Fawcett, Antonio (My University, 2019)
More than 50% of the world population live in the tropics mostly in developing countries, with great poverty and poor essential goods, services, and access. These conditions and environmental factors make the population high risk for a group of fungal, bacterial, and parasitic diseases, many of which affect the oral mucosa.
Keywords: Actinomycosis; Aspergillosis; Blastomycosis; Candidiasis; Coccidioidomycosis; Cryptococcus; Endemic syphilis; Fungal; Histoplasmosis; Leishmaniasis; Mucormycosis; Oral pathology; Paracoccidioidomycosis; Parasitic; Tropical; Yaws